STRATEGIC OPENNESS IN QUALITY CONTROL: ADJUSTING NPD STRATEGIC ORIENTATION TO OPTIMIZE PRODUCT QUALITY - Wimalachandra, Dinush Chanaka; Frank, Bjoern; Enkawa, Takao (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
Many innovative firms have shifted to an ‘open innovation’ strategy by using a wide range of external information. An emerging area in the literature on new product development (NPD) deals with strategies adopted by NPD departments to maximize product quality. This article tests and demonstrates that the open innovation paradigm can be extended to the area of product quality control practices in the NPD process. Using data collected in 10 countries, this study investigates the importance of external information acquired through B2B/B2C customer, competitor, technology, and manufacturing orientation in meeting quality and performance specifications of newly developed products, and the interconnected roles of B2B and B2C customer orientation in meeting these specifications. The results show that B2C customer orientation alone is not beneficial for meeting quality and performance specifications of newly developed products in B2B contexts, whereas in the presence of B2B affective information management, B2C customer orientation helps firms meet these specifications.